Amália tribute : fado original in Finnish = canto em finlandês - Härkönen, Tarja; Proenc; Rocket Records (Rocket Records, 2013)
Lauluja Amália Rodriguesin ohjelmistosta.
Keywords: Rodrigues, Amália : tribuutit; Rodrigues, Amália; 2010-luku; naiset; laulajat; kvinnor; sångare; Portugali; Suomi; Portugal; Finland